Diet of Hyphessobrycon auca (Pisces, characidae) in Iberá Wetland (Northeastern, Argentina) - Soneira, Paula (2011)
Hyphessobrycon auca Almiron, Casciotta, Bechara & Ruiz Diaz, 2004, inhabit small lakes located at the northwest of Ibera wetland in Argentina. This research describes some aspects of its feeding. Samples were collected from its type locality from 2007 to 2009. Analysis of 70 digestive tracts of individuals ranging from 24 to 56 mm standard length (SL) showed that higher plants, algae, and quironomids larvae dominated the diet in terms of relative volume and occurrence frequency. Therefore, this species was characterized as omnivorous, but there was a growing trend towards herbivory when size class incremed. Smaller size class (< 35 mm SL) fed on higher proportion of animal preys such as quironomids larvae and protozoans, in contrast to larger ones who consumed almost exclusively plants and algae.